The ides of April - Ray, Mary, 1932- (Warsaw, N.D. : Bethlehem Books ; San Francisco : Ignatius Press, 1999)
In Rome in 62 A.D., seventeen-year-old Hylas must find a way to save himself, his mother, and the other household slaves from imprisonment and imminent death when their master, a prominent senator, is found murdered.
"This edition slightly revised by the author"--T.p. verso.
Keywords: Slavery -- Rome -- Fiction; Rome -- Fiction